2008
DOI: 10.1080/14616730802113695
|View full text |Cite
|
Sign up to set email alerts
|

Representations of family relationships in children living with custodial grandparents

Abstract: Children's representations of family relationships were examined in relation to grandparent responsivity and depression, family sociodemographic risks, and children's behavior problems in custodial grandparent families. Using multiple methods, data were collected from 79 families with children aged 3 to 7.5 years. In 37 families, children were raised by grandparents as the result of maternal incarceration and, in 42 families, children lived with grandparents because of other parental problems. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 66 publications
2
34
0
1
Order By: Relevance
“…Research to date has examined the well-being of grandparents (Baker & Silverstein, 2008a;Butler & Zakari, 2005;Gerard, Landry-Meyer, & Roe, 2006;Hayslip & Glover, 2008;Leder, Grinstead, & Torres, 2007;Neely-Barnes, Graff, & Washington, 2010), health behaviors of grandparents (Baker & Silverstein, 2008b), the role of grandparents (Landry-Meyer & Newman, 2004), policies and laws affecting custodial grandparents (Bratteli, Bjelde, & Pigatti, 2008;Cox, 2009;Robinson-Dooley & Kropf, 2006;Van Etten & Gautam, 2012), services (Campbell, Carthron, Miles, & Brown, 2012;Collins, 2011;Cox, 2008;Kelley, Whitley, & Campos, 2010), the grandparentÀgrandchild relationship (Dolbin-MacNab & Keiley, 2006;Poehlmann et al, 2008), the health and achievement of grandchildren (Smith & Palmieri, 2007), and ethnic and cultural implications for grandfamilies (Carr, Hayslip, & Gray, 2012); Conway, Jones, & Speakes-Lewis, 2011;Kelch-Oliver, 2008). The literature has been primarily cross-sectional in nature and has focused on establishing an empiricallybased understanding of the needs of grandfamilies.…”
Section: Grandparents Raising Grandchildrenmentioning
confidence: 99%
“…Research to date has examined the well-being of grandparents (Baker & Silverstein, 2008a;Butler & Zakari, 2005;Gerard, Landry-Meyer, & Roe, 2006;Hayslip & Glover, 2008;Leder, Grinstead, & Torres, 2007;Neely-Barnes, Graff, & Washington, 2010), health behaviors of grandparents (Baker & Silverstein, 2008b), the role of grandparents (Landry-Meyer & Newman, 2004), policies and laws affecting custodial grandparents (Bratteli, Bjelde, & Pigatti, 2008;Cox, 2009;Robinson-Dooley & Kropf, 2006;Van Etten & Gautam, 2012), services (Campbell, Carthron, Miles, & Brown, 2012;Collins, 2011;Cox, 2008;Kelley, Whitley, & Campos, 2010), the grandparentÀgrandchild relationship (Dolbin-MacNab & Keiley, 2006;Poehlmann et al, 2008), the health and achievement of grandchildren (Smith & Palmieri, 2007), and ethnic and cultural implications for grandfamilies (Carr, Hayslip, & Gray, 2012); Conway, Jones, & Speakes-Lewis, 2011;Kelch-Oliver, 2008). The literature has been primarily cross-sectional in nature and has focused on establishing an empiricallybased understanding of the needs of grandfamilies.…”
Section: Grandparents Raising Grandchildrenmentioning
confidence: 99%
“…In the U.S., grandparent-headed households increased 30% from 1990 to 2000, and parents are entirely absent in many of these households (Simmons & Dye, 2000). Researchers have taken an interest in the wellbeing of the children and their grandparents in such special situations (Poehlmann, Park, Bouffiou, Abrahams, Shlafer, & Hahn, 2008;Ross & Aday, 2006). However, few studies have addressed the wellbeing or development of young children who live in normal families but are raised or co-parented by their grandparents.…”
Section: Prevalence Of Grandparents' Co-parentingmentioning
confidence: 99%
“…Compared with the children raised by young parents, those raised by grandparents tend to be involved in less social or outdoor activities due to the grandparents' physical weakness (Poehlmann et al, 2008;Li, 2013) and comparatively low social economic status (Fuller- Thompson, Minkler, & Driver, 1997). Thus, it is assumed that grandparents' co-parenting will influence children's pro-social behavior or reaction in strange situations.…”
Section: Children's Temperamentmentioning
confidence: 99%
“…Nevertheless, one of the most critical concerns faced by these children involves their development of mental health problems (Murray & Farrington, 2008b;Poehlmann et al, 2008). Indeed, several studies have shown anxiety, depression, and other internalizing problems to be common among children of incarcerated mothers (Geller, Garfinkel, Cooper, & Mincy, 2009;Kampfner, 1995;Phillips, Burns, Wagner, Kramer, & Robbins, 2002).…”
mentioning
confidence: 96%